2021
DOI: 10.3892/mco.2021.2413
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGF, EGF and HGF in early‑ and late‑stage colorectal cancer

Abstract: The heterogenous nature of colorectal cancer (CRC) highlights the need for a better understanding of the growth factors that affect tumour growth and cancer progression. The aim of the present study was to evaluate the role of epidermal growth factor (EGF), vascular endothelial growth factor (VEGF) and hepatocyte growth factor (HGF) in the early (I and II) and late (III and IV) stages of CRC. The serum levels and mRNA expression (n=30) of the aforementioned growth factors were measured and immunohistochemistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…However, macrophages have an important role in inflammatory-induced lymphangiogenesis. Studies have shown that the expression of VEGF-C and VEGF-D and their receptor VEGFR-3 in macrophages has a very significant correlation with the local LV density in tumors (33,34). In one study, the blockade of VEGF-C and VEGF-D signaling decreased obstruction-induced lymphangiogenesis, and the depletion of macrophages decreased lymphangiogenesis in the obstructed kidney (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, macrophages have an important role in inflammatory-induced lymphangiogenesis. Studies have shown that the expression of VEGF-C and VEGF-D and their receptor VEGFR-3 in macrophages has a very significant correlation with the local LV density in tumors (33,34). In one study, the blockade of VEGF-C and VEGF-D signaling decreased obstruction-induced lymphangiogenesis, and the depletion of macrophages decreased lymphangiogenesis in the obstructed kidney (35).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data demonstrate that levels of VEGF are in correlation with tumor stage. Therefore, it suggests a possible role of VEGF in the progression of the disease [ 40 ]. The published by Martini et al [ 41 ] showed that quantitative analysis of the VEGF-121 isoform, which is mainly detected in circulating blood, might be a predictor of response to anti-angiogenetic treatment.…”
Section: Possible Utilities Of Vegf Family Members In Colorectal Cancermentioning
confidence: 99%
“…Similar results were obtained in most recent studies conducted by Wang et al [ 45 ]. To the contrary, Abdulla et al [ 40 ] examined the expression of VEGF in tissues of CRC patients. Interestingly, the results have shown upregulation in the early-stage and downregulation in the late-stage of CRC in VEGF expression when compared to normal adjacent tissue.…”
Section: Possible Utilities Of Vegf Family Members In Colorectal Cancermentioning
confidence: 99%
“…186 High VEGF expression levels correlate with tumor stage and progression, linking them to CRC cases with a poor prognosis. 189 Various studies have implied the important role for VEGF overexpression in cancer. For example, two different splicing isoforms (VEGF121 and VEGF165) have been shown to be differentially expressed in CRC.…”
Section: Anti-tgf-β Strategies In Colorectal Cancer Stromal Cellsmentioning
confidence: 99%
“…Arguably the most influential of these are VEGFs and their receptor family (VEGF receptor, VEGFR), which play a vital part in angiogenesis, through the stimulation of endothelial cell proliferation and migration, influencing the permeability of blood vessels, and altering both the function and morphology of these 186 . High VEGF expression levels correlate with tumor stage and progression, linking them to CRC cases with a poor prognosis 189 . Various studies have implied the important role for VEGF overexpression in cancer.…”
Section: Role Of the Tumor Microenvironment Within Colorectal Cancermentioning
confidence: 99%